Food and foodways of medieval Cairenes : aspects of life in an Islamic metropolis of the eastern Mediterranean - Lewicka, Paulina B. (Islamic History and Civilization, 2011)
This is a pioneering study which analyzes the food cultures of medieval Cairenes on the basis of a large corpus of historical texts in Arabic. Individual chapters discuss what, why, and how the inhabitants of medieval Cairo ate what they did, and in which ways food shaped their everyday lives. Given the complex nature of "food" and "foodways" as areas of research, the book covers such diverse subjects as the genesis of the culinary culture of Egypt's capital and various practices related to food and eating. This monograph also considers several relevant social, political and economic circumstances in medieval Cairo, studying food culture in its broader context.